Pengaruh Rasio Kecukupan Modal, Likuiditas, Risiko Kredit dan Efisiensi Biaya Terhadap Profitabilitas Pada Bank Go Public - Uli Wildan Nuryanto; Anis Fuad Salam; Ratih Purnama Sari; Dede Suleman (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2020)
Abstract - This increase in economic growth does not necessarily increase the profitability of banks in Indonesia. There are three fundamental problems that have been unearthed by the Deposit Insurance Corporation (LPS) for banks, among others, the first decline in bank interest rates continuously causing bank interest margins to thin. Second, the regulatory burden requires banks to set aside capital for additional bank capital reserves and thirdly the potential increase in the risk of non-performing loans due to global economic uncertainty and the uneven recovery of the domestic economy. For this reason, this research was conducted to find out how much profitability of domestic banks listed on the Indonesia Stock Exchange in the period 2014-2018 and also the relationship between internal predictors which, according to the review study, had a significant effect on profitability. The population in this study were 43 banks listed on the Indonesia Stock Exchange in the 2014-2018 period while the sample was 10 banks listed on the IDX with the largest number of assets according to Bank Indonesia using the purposive sampling method. The results showed a significant CAR, LDR, NPL and BOPO significantly influence ROA. While partially LDR, NPL and BOPO have a significant effect on ROA while CAR has no significant effect. The magnitude of the effect of the predictor variable on profitability using the coefficient of determination obtained by 74.2% while the remaining 25.8% is influenced by other variables outside this research model.Keywords: Capital Adequacy Ratio (CAR), Liquidity Ratio (LDR), Credit Risk (NPL), Operational Cost Efficiency (BOPO). Profitability (ROA).